Memberdayakan Internet of Educational Things (IoET) untuk Mengembangkan Kapabilitas Digital bagi Guru-Guru SMP Wahid Hasyim - Thaariq, Zahid Zufar At; Nurdiyanto, Reno; Karima, Ummul; Utomo, Doni Anggoro Dwi Wahyu; Kuswandi, Dedi; Kesuma, Dany Wijaya; Putri, Chatur Erisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The COVID-19 pandemic has led to a digital-based learning shift, creating a significant learning gap in the Merdeka Curriculum era as face-to-face education resumes. SMP Wahid Hasyim Malang, like many others, faces challenges such as limited teacher-student interaction, reliance on traditional lectures, outdated resources, and underutilized internet facilities. To address this, we propose an Internet of Educational Things (IoET) empowerment program. Its goal is to establish a digital-based learning environment post-pandemic using hypercontent-based modules and Learning Management Systems (LMS) with IoET applications. Instructors will provide foundational training, and facilitators will offer ongoing mentoring. This program equips teachers with theoretical knowledge and practical skills, enhancing their ability to implement IoET-based learning models and media, improving their overall performance. Additionally, it will serve as a valuable reference for future educational services and research, becoming an alternative point of reference for various future educational endeavors and research initiatives.